Unveiling Hybrid Ameloblastoma: Uncommon Variant With Unique Diagnostic Challenges - Dilasha Dhungel; Varun Rastogi; Sandhya Chaurasia; Priyambada Karna (Clinical Case Reports)
ABSTRACT Ameloblastoma is a benign tumor originating from odontogenic tissue and has various histological subtypes. It accounts for approximately 18% of all odontogenic tumors. Hybrid ameloblastoma represents a combination of histopathological features from both desmoplastic ameloblastoma and conventional ameloblastoma, likely arising from the varying differentiation potentials of odontogenic epithelial cells, which may include follicular, acanthomatous, or plexiform types. It typically presents as a painless jaw swelling, leading to facial asymmetry, tooth mobility, root resorption, and tooth displacement. Radiographically, it appears as a mix of radiolucent and radiopaque areas. Hybrid ameloblastoma has an incidence of 1.1%. The variation within this lesion can complicate both diagnosis and treatment. This report highlights two cases of hybrid ameloblastoma: a male in his 60s presenting with a swelling in the lower right jaw and a female in her 50s with a similar swelling in the same region.